Penerapan Metode Phonetic Placement untuk Gangguan Artikulasi pada Anak dengan Disabilitas Intelektual: Studi Kasus Tunggal - Jumiarti, Jumiarti; Nur Muslimah, Addinia; Reza Antafani, Alfa; Budi, Ery (Jurnal Terapi Wicara, 2023)
Speech intelligibility is an important factor in verbal communication. Children with intellectual disabilities with intellectual disabilities will face difficulties in communicating due to reduced speech intelligibility. This condition will affect social skills, mental mental state, and academics. Articulatory misplacement is one of the factor that makes difficulties in articulation accuracy.